Midlife body mass index, central adiposity and neuropsychological performance over 10 years in women living with and without HIV - Vásquez, Elizabeth; Kuniholm, Mark H.; Appleton, Allison A.; Rubin, Leah H.; Adimora, Ada A.; Fischl, Margaret A.; Fox, Ervin; Mack, Wendy J.; Holman, Susan; Moran, Caitlin Anne; Minkoff, Howard; Plankey, Michael W.; et al. (Frontiers in Endocrinology, 2023)
Observations of overweight and obesity in association with neuropsychological performance (NP) vary over the adult life course depending on baseline levels, biological sex, age, race, temporality of measurements, and other factors. Therefore, similar published analyses across cohorts are inconsistent. In our sample of women living with HIV infection (WLWH) and women without HIV (WWOH), we conducted comparable analyses as those published in men with and without HIV infection. We examined cross-sectional and longitudinal associations between body mass index (BMI) and waist circumference (WC) and NP. Methods. Four hundred thirty two 432 virologically-suppressed WLWH and 367 WWOH, >40 years in the Women’s Interagency HIV Study (WIHS) with anthropometry and NP assessments every two years from 2009-2019 were included in the study. Demographically-adjusted T-scores were calculated for six NP domains: learning, memory, executive function, processing speed, attention and working memory, and motor function. Multivariable linear regression models stratified by HIV status were used to examine cross-sectional associations of BMI and WC by NP domain; repeated measures analyses assessed baseline BMI and WC in association with longitudinal change in NP. Covariates included sociodemographic, behavioral, and HIV-related characteristics. Results At baseline among all women, the median age was 45 years 65% were Non-Latinx Black women, and 45% were obese women. Obese WLWH (BMI>30.0 kg/m2) had poorer executive function (β=-2.27, 95%CI [-4.46, -0.07]) versus WLWH with healthy BMI (18.5–24.9 kg/m2). Longitudinally over ~8 years, obese versus overweight WWOH improved on memory (β=2.19, 95%CI [0.13, 4.26]), however overweight versus healthy WWOH experienced declining memory (β= -2.67, 95%CI [-5.40, -0.07]). Increasing WC was associated with declining executive, processing speed, and motor function (p’s<0.05); an at-risk WC was associated with improved memory (β=1.81, 95%CI [0.19, 3.44]) among WWOH. Among WLWH, increasing BMI was associated with improved learning (β=0.07, 95%CI [0.00, 0.15]. Conclusions Our cross-sectional and longitudinal analyses evaluating the associations of BMI and WC and NP were mixed compared to previous reports. This illustrates the importance of sociodemographic characteristics, baseline levels of exposures and outcomes, HIV status, temporality of measurements, and other factors when evaluating aging HIV epidemiology study results.